Student wellbeing and academic support in higher education - Wilson Fadiji, Angelina; Eloff, Irma (Frontiers in Education, 2024)
This study reports on the synergistic liaison between student wellbeing and academic support in higher education. The study took place at a large, urban university in South Africa within the context of the COVID-19 pandemic. Brief interviews were conducted between September and November 2021, with undergraduate students (n = 645, Mage = 22; SD = 2) from a variety of scientific fields. The guiding question for the brief interviews was, ‘What contributes to your wellbeing at the university?’ Responses were captured in statu nascendi (as it develops) by fieldworkers from the helping professions and then transferred to a comprehensive Electronic Data Sheet. The raw verbal response data were analyzed using an open coding process where major and minor themes were initially indicated. A theme emerged around the intricacies of academic support and intrapersonal processes that are central to the wellbeing of students in higher education. Academic support was apparent in the provisioning of resources for learning, quality communication from lecturers, peer-to-peer support, and collective positive student experiences. Beyond these external resources, intrapersonal factors including a focus on the self, a sense of responsibility, and ensuring mental balance, while sustaining a sense of accomplishment academically, emerged as critical to student wellbeing. Efforts to continually improve student experience are still paramount within the higher education space, and this can be accompanied by psychosocial interventions aimed at promoting a strong sense of positive selfhood. These interventions could be designed to promote internal resources that allow students to capitalize on institutional provisioning in the achievement of academic goals and wellbeing.